ANALISIS EFEKTIVITAS DAN PEMANFAATAN DANA DESA DI KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU - Imayyah Witri; Hamidi Wahyu; Isbah Ufira (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to determine the effectiveness of village funds and utilization of village funds in Batang Gansal District, Indragiri Hulu Regency in 2015-2018. In collecting this research data using techniques with documentation, literature study and interviews. The analytical method used in this research is descriptive method with quantitative approach. Where descriptive describes the effectiveness and use of village funds. While quantitative by calculating the growth of village funds per one year with the aim to find out the effectiveness of village funds per one year. The results showed that the use of village funds in Batang Gansal Subdistrict in general was already good because the realization of the budget approached the target budget set, meaning that the use of village funds in general could be said in accordance with the objectives. The effectiveness of village funds in Batang Gansal District, Indragiri Hulu in 2015-2018 was declared effective in terms of percentage results of more than 90%. The Village Fund is allocated for village development, that is physical development and community empowerment. Utilization of village funds in Batang Gansal District based on data obtained from the village office, the use of village funds in 2015- 2018 is used for village development activities, especially physical development and village funds are used for community empowerment.Keywords: Effectiveness, Village Fund